RANCANGAN SISTEM KONTROL MANAJEMEN PERSEDIAAN TOKO BINTANG TERANG - Cathalina Halim (Business Administration Department - Universitas Katolik Parahyangan, 2022)
This study aims to design an inventory management control system at Toko Bintang Terang. This research uses a qualitative approach of the Toko Bintang Terang. Data analysis tools use MIT 90's Framework and Data Flow Diagrams. Data sources come from interviews with owners and managers and also observations. The results showed that there were 4 groups of activities related to the inventory control system namely: store planning, purchasing, warehousing, and logistics. The proposed system for store planning is in the form of inventory categorization based on 3 factors, namely movement of goods, consumer tastes, and events. The purchasing system is categorized into 2 processes ordering systems such as by telephone or salesmen who come to the store. The warehouse system needs to implement stock opname that has not been done so far as well as a logistics system that helps companies save costs and improve services to customers. This system can run optimally if store owners and managers carry out routine monitoring and checking of inventory management processes such as categorizing goods per month, operating inventory every month, and checking logistics whether it is in accordance with the planned budget or not.